2017
DOI: 10.3389/fpsyg.2017.01922
|View full text |Cite
|
Sign up to set email alerts
|

Love Influences Reproductive Success in Humans

Abstract: As love seems to be universal, researchers have attempted to find its biological basis. However, no studies till date have shown its direct association with reproductive success, which is broadly known to be a good measure of fitness. Here, we show links between love, as defined by the Sternberg Triangular Theory of Love, and reproductive success among the Hadza—traditional hunter-gatherer population. We found that commitment and reproductive success were positively and consistently related in both sexes, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 56 publications
(84 reference statements)
2
22
0
3
Order By: Relevance
“…The outcomes of this study are consistent with the results found by Sorokowski et al [26], as we also found an unexpected negative correlation between the women’s intimacy scores and the number of children, although this correlation was not statistically significant. It is likely that women that need to look after more children have less time to spend with their partners, which explains this lower level of intimacy.…”
Section: Discussionsupporting
confidence: 93%
“…The outcomes of this study are consistent with the results found by Sorokowski et al [26], as we also found an unexpected negative correlation between the women’s intimacy scores and the number of children, although this correlation was not statistically significant. It is likely that women that need to look after more children have less time to spend with their partners, which explains this lower level of intimacy.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings raise implications about romantic passion in the form of a kiss, within human pair-bonds. Although kissing, in contrast to romantic passion, is not a human universal 11 (see also 33 ) data from remote societies suggests that social complexity, indexed via stratification, predicts the likelihood of observing romantic kissing in that culture 11 (same dataset as used in 27 ). Social complexity and increased group competition for scarce resources was thought to be a key driver in the evolution of human social intelligence, selecting for those who could monitor relations between group members as groups increased in size 34 .…”
Section: Discussionmentioning
confidence: 99%
“…To summarize, the results of this research suggest that romantic love may be related to hormonal changes in women, which may not only facilitate pair bonding and commitment, as shown in previous research [5,6,7,8,9,10], but could also potentially increase a woman’s fecundity. As such, physiological changes that occur when falling in love may be adaptive and may potentially increase a couple’s probability of conceiving offspring [47]. This adaptive interpretation may, at least partially, explain why romantic love is observed ubiquitously across diverse human cultures [48,49,50].…”
Section: Discussionmentioning
confidence: 99%